The activity of the Academy of sciences in the field of geological and geographical exploration of the Soviet Union: report delivered by V. A. Obruchev to the 220th anniversary meeting of the Academy of sciences of the USSR - Обручев В. А. Владимир Афанасьевич (Moscow, Academy Press, 1945)
To the 220th anniversary meeting of the Academy of Sciences of the USSR